GERM CELL TUMORS OVARIUM - Lintong, Poppy M. (Jurnal Biomedik : JBM, 2010)
Abstract: Germ cell tumors of the ovary are primary ovarian tumors which derived from primitive germinal cells. These tumors are derived from primitive germinal cells. The total incidence of these tumors is around 30% of all tumors, and are mostly found in children and young adults. The etiology and pathogenesis  of these tumors are not clearly defined, but some studies have shown that etiology is related to genetic origin. WHO classification divides these germ cell tumors of the ovarian into two groups: dysgerminoma and the other ovarian germ cell tumors, which consist of pure types and mixed types. The pure type consists of endodermal sinus tumor, embryonal carcinoma, polyembryoma, choriocarcinoma, anda teratoma. Dysgerminoma is the most frequent malignant type. This tumor has characteristic microscopic features and different histo-logical variants, which sometimes leads to difficulty in making a diagnosis. Immuno-histochemical tests are needed for making several differential diagnoses and finding the most appropriate diagnosis. Pathological examination of tissues and ascites fluid are also important in determi-nation of the clinical stages, which play some important roles in managing the therapy and prognosis. Keywords: germ cell tumors, ovarium, pathogenesis, classification, dysgerminoma.     Abstrak: Germ cell tumors ovarium merupakan tumor primer ovarium yang berasal dari sel-sel germinal primitif. Insidennya kira-kira 30% dari seluruh tumor ovarium, dan teruta-ma menyerang anak-anak dan dewasa muda. Etiologi dan patogenesis dari germ cell tumors ovarium belum diketahui dengan jelas, namun beberapa studi telah menunjukkan  bahwa hal ini ada hubungannya dengan etiologi genetik. Menurut klasifikasi WHO germ cell tumors ovarium digolongkan atas dua bagian besar yaitu dysgerminoma, dan germ cell tumors ovarium lainnya, yang terdiri dari bentuk murni dan campuran. Bentuk murni terdiri dari endodermal sinus tumor, embryonal carcinoma, polyembryoma, chorio-carcinoma, dan teratoma. Dysgerminoma merupakan germ cell tumors ovarium ganas tersering. Tumor ini mempunyai ciri-ciri mikroskopik yang karakteristik dan varian histologik berbeda-beda, yang kadang-kadang dapat menimbulkan problem diagnostik karena sulit dibedakan dengan jenis tumor yang lain. Dalam melakukan diagnosis banding  dan menegaskan diagnosis secara pasti perlu dilakukan pemeriksaan imunohistokimia. Pemeriksaan patologi jaringan dan sitologi cairan asites  penting dalam penentuan stadium klinik, dan hal ini berpengaruh terhadap pilihan pengobatan dan prognosis penderita. Pada tulisan ini selain  dibahas tentang germ cell tumors ovarium secara umum, juga dibahas salah satu germ cell tumors ovarium yang tersering yaitu dysgerminoma. Kata kunci: germ cell tumors, ovarium, patogenesis, klasifikasi, dysgerminoma.